2003
DOI: 10.1021/ma021608q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thymine-Functionalized Polystyrenes for Applications in Biotechnology. Polymer Synthesis and Characterization

Abstract: Novel polystyrenes (PS) carrying thymine functional groups were synthesized by copolymerizing styrene (St) and 1-(vinylbenzyl)thymine (1-VBT) in the presence and absence of divinylbenzene (DVB) in batch free radical emulsion polymerization. Microsphere latexes were obtained with an average particle size of ≈60 nm (3.0 and 5.0 wt % [VBT] 0) with ≈80% conversion and ≈38 nm (10 wt % [VBT]0) with 91% conversion. The final copolymer latexes were freeze-dried to obtain particles in the size range of 32-544 µm. Copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…From the GPC analysis it is likely that cross-linked network copolymers from bisVBT monomers will not be soluble, and therefore the observed GPC traces of filtered samples represent the soluble fraction of the materials with low degree of cross-linking. This might explain the unexpectedly low polydispersity (Pd) values of the copolymer molecular weights, compared to reported random VBT-VBA copolymerization reactions, which exhibit acceptable polydispersity values between 1.5 and 4 [3,26,28,29].…”
Section: Gel Permeation Chromatographymentioning
confidence: 85%
See 2 more Smart Citations
“…From the GPC analysis it is likely that cross-linked network copolymers from bisVBT monomers will not be soluble, and therefore the observed GPC traces of filtered samples represent the soluble fraction of the materials with low degree of cross-linking. This might explain the unexpectedly low polydispersity (Pd) values of the copolymer molecular weights, compared to reported random VBT-VBA copolymerization reactions, which exhibit acceptable polydispersity values between 1.5 and 4 [3,26,28,29].…”
Section: Gel Permeation Chromatographymentioning
confidence: 85%
“…The study of bioinspired environmentally benign, nontoxic, and recyclable thymine-based polymers has been on a steady rise in the past decades, due to their photosensitivity and molecular recognition patterns [1][2][3][4]. A specific example of such a molecule is 1-(4-vinylbenzyl)thymine (VBT) [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 The polymers were prepared via free-radical emulsion copolymerization of styrene and 1-(vinylbenzyl)thymine (1-VBT). XPS analysis showed that the thymine content was much higher on the surface (7-20 mol %) than in the bulk (1-4 mol %) of the PS-VBT polymers.…”
Section: Protein-adsorption Studiesmentioning
confidence: 99%
“…In addition, the existence of natural mechanisms to reverse the photo-dimerization reaction and to restore the polymers to their original state provides exciting opportunities to create fully recyclable materials (14). Some practical applications involve hair-styling products (11), electrically conductive coatings (13), antibacterial-coated surfaces (12), controlled-release drug-delivery systems (16,19), recyclable plastics (10,14), and photo-resists (5Á8,15) including fabrication of electronic components and printed circuit boards. Besides the large variety of potential applications, these thymine-based PS are environmentally-benign and consistent with the Twelve Principles of Green Chemistry (1): a non-toxic, water-soluble, and biodegradable material, which requires low energies for processing (20).…”
mentioning
confidence: 99%